Thyroid Function of Pregnant Women and Perinatal Outcomes in North Macedonia - Avramovska, Maja; Kostova, Neda Milevska; Karanfilski, Borislav; Hunziker, Sandra; Vaskova, Olivija; Dimitrov, Goran; Dzikova, Elena; Markova, Ana Daneva; Lega, Marija Hadzi; Tofoski, Gligor; Sikole, Aleksandar (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective Thyroid diseases are the second most common endocrine disorders in the reproductive period of women. They can be associated with intrauterine growth restriction (IUGR), preterm delivery, low Apgar score, low birthweight (LBW) or fetal death. The aim of the present study is to explore thyroid dysfunction and its relationship with some poor perinatal outcomes (Apgar Score, low birthweight, and preterm delivery).Methods Dried blood spot samples from 358 healthy pregnant women were analyzed for thyroid stimulating hormone (TSH), total thyroxine (TT4), and thyroglobulin (Tg). Neonatal data were collected upon delivery. Four groups were formed based on thyroid function tests (TFTs).Results Of the 358 tested women, 218 (60.72%) were euthyroid. Isolated hypothyroxinemia was present in 132 women (36.76%), subclinical hyperthyroidism in 7 women (1.94%), and overt hypothyroidism in 1 (0.28%). The perinatal outcomes IUGR (p = 0.028) and Apgar score 1 minute (p = 0.015) were significantly different between thyroid function test [TFT]-distinct groups. In the multiple regression analysis, TT4 showed a statistically significant inverse predictive impact on LBW (p < 0.0001), but a positive impact of Tg on LBW (p = 0.0351).Conclusion Thyroid hormones alone do not have a direct impact on neonatal outcomes, but the percentage of their participation in the total process cannot be neglected. Based on the regression analysis, we can conclude that TT4 and Tg can be used as predictors of neonatal outcome, expressed through birthweight and Apgar score. The present study aims to contribute to determine whether a test for thyroid status should become routine screening during pregnancy.
Keywords: thyroid stimulating hormone; total thyroxine; thyroglobulin; perinatal outcomes; low birth weight